Education and Communication Technologies in Nursing teaching during the COVID-19 pandemic: Integrative Review (Research, Society and Development, 2021)
Objective: to know the educational and communication technologies used in nursing education during the COVID-19 pandemic, as well as to reflect how each technology contributed to the teaching-learning process in this scenario. Methodology: This is an integrative literature review. The electronic search was performed in the Virtual Health Library, MEDLINE / PubMed, Cumulative Index to Nursing and Allied Health Literature and Web of Science databases with the keywords selected in the Health Science Descriptors and Medical Subject Headings. Results: 80 studies were found, after applying the eligibility criteria, 8 articles remained for the synthesis. In this study, we identified the use of different technologies for teaching nursing, highlighting clinical simulation in a virtual environment, digital teaching platforms and online communication platforms. Conclusion: The use of these technologies proved to be efficient to replace traditional models of learning during the health crisis caused by the new coronavirus, however difficulties were evidenced in the incorporation of these tools by students and teachers, mainly related to problems of infrastructure and technological training of educators.